Efektivitas Pendekatan Konseling Kognitif-Perilaku dalam Mengurangi Perilaku Bullying di Sekolah - Musfiroh, Sri; Mubarok, Ahmad Shofi; Rahmatika, Siti Difta; Lestari, Ayu; Novianto, Erik (Westscience Press, 2024)
Bullying behavior in schools remains a significant challenge, impacting students' well-being, social relationships, and academic success. This study explores the effectiveness of a cognitive-behavioral counseling (CBC) approach in reducing bullying behavior through qualitative analysis involving five informants, including school counselors and students. Data were collected via semi-structured interviews and analyzed using NVIVO software to identify key themes. The findings indicate that CBC effectively reduces bullying behavior by improving emotional regulation, fostering empathy, and enhancing conflict resolution skills. However, practical challenges such as time constraints, limited resources, and stigma surrounding counseling were identified. These findings provide valuable insights for educators and policymakers to develop evidence-based strategies for addressing bullying behavior and promoting a safer school environment.